THE USE OF BIOLOGICAL TREATMENT IN RHEUMATOID ARTHRITIS – A REVIEW OF THE CURRENT LITERATURE - Anna Bereta-Kostaś; Hubert Kostka; Jadwiga Kleinrok; Damian Dolata; Adrian Zagórski; Rafał Kuśmider; Małgorzata Leśnik; Patrycja Wierzbowska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Rheumatoid arthritis (RA) is a chronic inflammatory disease of autoimmune origin, with an estimated global prevalence of approximately 1% of the population. It can lead to progressive cartilage and bone destruction, ultimately resulting in disability and contributing to premature mortality. Brief description of the state of knowledge: The disease most commonly develops in individuals between the ages of 30 and 50. In the majority of patients, it follows a relapsing-remitting course, characterized by alternating periods of exacerbation and remission, with gradual joint destruction over time. The most characteristic symptoms include morning stiffness lasting longer than one hour, joint pain and swelling. Rheumatoid arthritis typically affects the small joints of the hands and feet. Diagnostic evaluation often reveals symmetric polyarthritis, particularly involving the wrists, hands and feet, consistent with inflammatory joint disease. Delays in establishing a correct diagnosis are common and may result from patients underestimating their symptoms. The introduction of biologic agents in RA therapy represents a major advancement and offers significant potential for effective disease control and improved patient outcomes. Conclusions: Rheumatoid arthritis, an increasingly common condition in medical practice, must be diagnosed as soon as possible to halt the progressive effects of inflammation and prevent irreversible complications. Knowledge of risk factors, symptoms and new drug therapies is key to making an accurate diagnosis. The prospects for the use of biologics are extremely promising, as patients achieve a faster and more complete response to treatment while generating lower costs than with standard, long-term conventional treatment.